Body image perceptions and avoidance behaviours among a Moroccan group of adolescents - Raja Zakaria; Hakima Amor; Abdellatif Baali (Taylor & Francis Group, 2022)
Background Adolescents are a vulnerable group to body dissatisfaction that causes unhealthy attitudes and behaviours. It has been shown that many factors affect body image dissatisfaction. Aim To describe body image size perception, degree of body dissatisfaction, avoidance behaviours, and their relationship with gender, age, and weight status, and to assess the relationship between body dissatisfaction and avoidance behaviours among a group of Moroccan adolescents. Subjects and methods This cross-sectional survey was comprised of a sample of 487 adolescents. Stunkard's Figure Rating Scale was used to assess perceptions of current and ideal body image and body dissatisfaction. Body Image Avoidance Questionnaire was employed to assess avoidance behaviours. Results Body dissatisfaction was found to be strongly associated with weight status in both male and female adolescents. Avoidance behaviours were positively associated with gender, age, weight status, and body dissatisfaction. Indeed, avoidance behaviours were frequently reported among females, young adolescents, those with high BMI z-score, and those seeking to lose weight. Adolescents tended to behave under the influence of two factors: clothing and weighing-grooming. Conclusion Weight status is an important factor that deeply impacts adolescent body dissatisfaction. Adolescents resort to behaviour avoidance and physical appearance control to cope with body dissatisfaction.